Specific features of difficult airways in patients with face and neck burns - A. V. Korneev; S. A. Orudzheva; A. N. Kudryavtsev (Вестник анестезиологии и реаниматологии)
The problem of difficult airways remains relevant for many years. Complications associated with unpredictable difficult airways often lead to the lethal outcome or neurological problems. This article analyzes the causes of difficult airways in patients with burns of face and neck. Such patients face a higher risk to develop difficult airways and it is impossible to follow the traditional procedure for maintaining airway patency. The article expresses the opinion about the inability of modern methods for assessing airway patency to predict possible problems associated with tracheal intubation and ventilation of patients with burns of face and neck.